2022
DOI: 10.1107/s2053229622008518
|View full text |Cite
|
Sign up to set email alerts
|

77Se and 125Te solid-state NMR and X-ray diffraction structural study of chalcogen-bonded 3,4-dicyano-1,2,5-chalcogenodiazole cocrystals

Abstract: Three novel chalcogen-bonded cocrystals featuring 3,4-dicyano-1,2,5-selenodiazole (C4N4Se) or 3,4-dicyano-1,2,5-tellurodiazole (C4N4Te) as chalcogen-bond donors and hydroquinone (C6H6O2), tetraphenylphosphonium chloride (C24H20P+·Cl−) or tetraethylphosphonium chloride (C8H20P+·Cl−) as chalcogen-bond acceptors have been prepared and characterized by single-crystal X-ray diffraction (XRD), powder X-ray diffraction and 77Se/125Te magic-angle spinning solid-state NMR spectroscopy. The single-crystal XRD results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…= 7.07%) is the preferred isotope over 123 Te (γ = −7.06 × 10 7 rad s –1 T –1 ; Ξ = 26.17%, N.A. = 0.89%) due to its higher natural abundance and frequency ratio, and yields sharp NMR line shapes with excellent resolution over a large chemical shift window of ∼5000 ppm that is sensitive to different electronic structures and Te oxidation states in various organo- and inorganic tellurium compounds. …”
Section: Resultsmentioning
confidence: 99%
“…= 7.07%) is the preferred isotope over 123 Te (γ = −7.06 × 10 7 rad s –1 T –1 ; Ξ = 26.17%, N.A. = 0.89%) due to its higher natural abundance and frequency ratio, and yields sharp NMR line shapes with excellent resolution over a large chemical shift window of ∼5000 ppm that is sensitive to different electronic structures and Te oxidation states in various organo- and inorganic tellurium compounds. …”
Section: Resultsmentioning
confidence: 99%
“…It has been understood for some time that the formation of an HB induces changes in the chemical shielding of not only the bridging proton but also neighboring atoms such as the atom bonded to H and the electron-donating base atom. More recent work has documented evidence that the formation of other noncovalent bonds that are closely related to HBs, such as halogen and chalcogen bonds, also induces clear shifts in the NMR signal of the atoms involved. Of this set of atoms, the one that appears to bear the closest correlation with the strength of the bond is the electron donor atom, ,, which in this case would be the N of NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[36] The ChB runs a full spectrum of bond strength [40] with Te being particularly strong, [41] and reveals itself in a number of ways including solid state NMR. [42,43] A good deal of our present understanding of the ChB is contained in a number of recent review articles [24,[44][45][46][47][48] to which an interested reader is referred.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing research has revealed the occurrence of these bonds in biomolecules such as proteins and nucleic acids [21,35–39] or SAM riboswitches [36] . The ChB runs a full spectrum of bond strength [40] with Te being particularly strong, [41] and reveals itself in a number of ways including solid state NMR [42,43] . A good deal of our present understanding of the ChB is contained in a number of recent review articles [24,44–48] to which an interested reader is referred.…”
Section: Introductionmentioning
confidence: 99%